Exploring Alternative Teaching and Learning Platforms in Post-COVID-19 - Ozioma Roseline Umera; Stacey Omeleze Baror (Online Learning In Educational Research (OLER), 2025)
Learning for undergraduate students at the National Open University of Nigeria (NOUN), Gwagwalada study center, has significantly shifted toward e-learning since the COVID-19 pandemic. This study investigates how NOUN students use e-learning platforms and the challenges they face. Using a survey design with qualitative methods, data from 364 participants were collected through questionnaires and interviews. Guided by the Technology Acceptance Theory, the study finds that students predominantly use emails, LMS, video conferencing, and social media for academic activities. Key benefits include flexibility, convenience, equitable access, and enhanced critical thinking. However, infrastructure and policy gaps persist. The study highlights the importance of ongoing improvements in e-learning systems and recommends that NOUN regularly conduct faculty training and digital literacy workshops to enhance participation and reduce barriers